Comparative In Vitro Study: Assessing Phytochemical, Antioxidant, Antimicrobial, and Anticancer Properties of Vaccinium macrocarpon Aiton and Vaccinium oxycoccos L. Fruit Extracts - Rima Šedbarė; Valdimaras Janulis; Alvydas Pavilonis; Vilma Petrikaite (MDPI AG, 2024)
The phytochemical diversity and potential health benefits of V. oxycoccos and V. macrocarpon fruits call for further scientific inquiry. Our study aimed to determine the phytochemical composition of extracts from these fruits and assess their antioxidant, antibacterial, and anticancer properties in vitro. It was found that the ethanolic extracts of V. oxycoccos and V. macrocarpon fruits, which contained more lipophilic compounds, had 2-14 times lower antioxidant activity compared to the dry aqueous extracts of cranberry fruit, which contained more hydrophilic compounds. All tested cranberry fruit extracts (OE, OW, ME, and MW) significantly inhibited the growth of bacterial strains S. aureus, S. epidermidis, E. coli, and K. pneumoniae in vitro compared to the control. Cytotoxic activity against the human prostate carcinoma PPC-1 cell line, human renal carcinoma cell line (CaKi-1), and human foreskin fibroblasts (HF) was determined using an MTT assay. Furthermore, the effect of the cranberry fruit extract samples on cell migration activity, cancer spheroid growth, and viability was examined. The ethanolic extract from V. macrocarpon fruits (ME) showed higher selectivity in inhibiting the viability of prostate and renal cancer cell lines compared to fibroblasts. It also effectively hindered the migration of these cancer cell lines. Additionally, the V. macrocarpon fruit extract (ME) demonstrated potent cytotoxicity against PPC-1 and CaKi-1 spheroids, significantly reducing the size of PPC-1 spheroids compared to the control. These findings suggest that cranberry fruit extracts, particularly the ethanolic extract from V. macrocarpon fruits, have promising potential as natural remedies for bacterial infections and cancer therapy.